2019
DOI: 10.1002/jso.25586
|View full text |Cite
|
Sign up to set email alerts
|

Targeted muscle reinnervation in oncologic amputees: Early experience of a novel institutional protocol

Abstract: Background We describe a multidisciplinary approach for comprehensive care of amputees with concurrent targeted muscle reinnervation (TMR) at the time of amputation. Methods Our TMR cohort was compared to a cross‐sectional sample of unselected oncologic amputees not treated at our institution (N = 58). Patient‐Reported Outcomes Measurement Information System (NRS, PROMIS) were used to assess postamputation pain. Results Thirty‐one patients underwent amputation with concurrent TMR during the study; 27 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 95 publications
2
124
0
Order By: Relevance
“…At the time of the latest follow-up, 85% (17 of 20) of the patients with a lower-extremity amputation and 40% (2 of 5) of the patients with an upper-extremity amputation reported daily prosthetic use. This is comparable with the findings of prior work by the senior author regarding TMR for all indications, which demonstrated an 80% prosthesis wear rate at 3.4 months postoperatively 44 . Furthermore, in the current study, we found a 36% rate of self-reported unemployment due to disability.…”
Section: Discussionsupporting
confidence: 89%
“…At the time of the latest follow-up, 85% (17 of 20) of the patients with a lower-extremity amputation and 40% (2 of 5) of the patients with an upper-extremity amputation reported daily prosthetic use. This is comparable with the findings of prior work by the senior author regarding TMR for all indications, which demonstrated an 80% prosthesis wear rate at 3.4 months postoperatively 44 . Furthermore, in the current study, we found a 36% rate of self-reported unemployment due to disability.…”
Section: Discussionsupporting
confidence: 89%
“…The efficacy of TMR and RPNI in treating neuropathic pain has been previously reported, with improved pain scores and outcomes compared with those of cohorts undergoing traditional traction neurectomies and cohorts undergoing “burying nerves in the surrounding muscle.” 12 , 16 , 17 We believe that TMRpni may have advantages compared with TMR or RPNI alone. RPNI is limited by the size of the free muscle graft.…”
Section: Discussionmentioning
confidence: 91%
“…Any patient who is a candidate for TMR is eligible for TMRpni, including adult and pediatric patients requiring amputation for traumatic, oncologic, infectious, or dysvascular indications. 17 , 18 TMRpni can be performed at the time of amputation for neuropathic pain prevention and improved intuitive prosthetic control, or as a delayed treatment. TMR has been described for below and above knee, transradial and transhumeral, and forequarter and hindquarter amputations, as well as for treatment of neuroma without any associated amputation.…”
Section: Indicationsmentioning
confidence: 99%
“…5 Targeted muscle reinnervation (TMR) is a nerve transfer technique where proximal stumps of the transected major peripheral nerves are transferred to recipient redundant motor nerves within adjacent muscles of the amputated limb. [1][2][3][6][7][8] TMR purposefully redirects the major peripheral nerve into an intact nerve and accompanying freshly de-innervated neuromuscular junction, thus providing a target into which the regenerating major peripheral nerve may grow rather than forming a painful neuroma. [1][2][3][6][7][8] This technique provides viable end-organs (Golgi apparatus) for the transected nerves to reinnervate, mitigating the mechanism for symptomatic neuroma complications seen in traditional traction neurectomy by limiting the nerve-scar interface and sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…TMR confers a functional destination for regenerating axons via trophic stimulation, satisfying the nerve ending to lessen and/or prevent the development of neuropathic pain. 1,4,[6][7][8] As such, the concept of TMR is analogous to grounding a live electrical wire. 1 Historically, TMR has provided additional benefits by increasing electromyography (EMG) signal generators for advanced myoelectric prostheses.…”
Section: Introductionmentioning
confidence: 99%